The Emerging Paradigm of Leadership for Future: The Use of Authentic Leadership to Lead Innovation in VUCA Environment - Khan, Muhammad Mumtaz; Ahmed, Syed Saad; Khan, Essa (Frontiers in Psychology, 2021)
The purpose of this study was to ascertain the role of leader-member exchange and identification with the leader as parallel mediators linking authentic leadership with innovative work behavior of the employees. The data were collected from three sectors of the service industry. The final sample size obtained was 347. The data were collected both through google form and pen-filled questionnaires. SPSS was used to compute demographic profiles and conduct hierarchal regression while Smart-PLS was used for evaluating the constructs for their psychometric properties and testing the structural relations as proposed in the model. The study found leader-member exchange and identification with the leader to mediate between authentic leadership and innovative work behavior of the employees. The current study found leader-member exchange and identification with the leader to be the mediators between authentic leadership and innovative work behavior.